The D2/3 dopamine receptor in pathological gambling: a positron emission tomography study with [11C]‐(+)‐propyl‐hexahydro‐naphtho‐oxazin and [11C]raclopride. (3rd January 2013) - Boileau, Isabelle; Payer, Doris; Chugani, Bindiya; Lobo, Daniela; Behzadi, Arian; Rusjan, Pablo M.; Houle, Sylvain; Wilson, Alan A.; Warsh, Jerry; Kish, Stephen J.; Zack, Martin
Abstract Aims Pathological gambling (PG) shares diagnostic features with substance use disorder (SUD), but the neurochemical mechanisms underlying PG are poorly understood. Because dopamine (DA), a neurotransmitter implicated in reward and reinforcement, is probably involved, we used positron emission tomography (PET) to test whether PG is associated with abnormalities in D2 and D3 receptor levels, as observed in SUD. Design Case–control study comparing PG to healthy control (HC) subjects. Setting Academic research imaging centre. Participants Thirteen non‐treatment‐seeking males meeting DSM‐IV criteria for PG, and 12 matched HC (11 of whom completed PET). Measurements Two PET scans (one with the D3 receptor preferring agonist [11C]‐(+)‐propyl‐hexahydro‐naphtho‐oxazin (PHNO) and the other with [11C]raclopride) to assess D2/3 DA receptor availability, and behavioural measures (self‐report questionnaires and slot‐machine game) to assess subjective effects and relationships to PET measures. Findings Binding of both radiotracers did not differ between groups in striatum or substantia nigra (SN) (all P > 0.1). Across PG, [11C]‐(+)‐PHNO binding in SN, where the signal is attributable primarily to D3 receptors, correlated with gambling severity (r = 0.57, P = 0.04) and impulsiveness (r = 0.65, P = 0.03). In HC, [11C]raclopride binding in dorsal striatum correlated inversely with subjective effects of gambling (r = −0.70, P = 0.03) and impulsiveness (r = −0.70, P = 0.03). Conclusions Unlike with substance use disorder, there appear to be no marked differences in D2/D3 levels between healthy subjects and pathological gamblers, suggesting that low receptor availability may not be a necessary feature of addiction. However, relationships between [11C]‐(+)‐PHNO binding and gambling severity/impulsiveness suggests involvement of the D3 receptor in impulsive/compulsive behaviours.